Identification Of Learning Styles Of Santri And Non-Santri Students Of Sma Plus Darul Hikmah - M. Aditiya Silvatama; Indah Wahyuni (Tinta Emas Publisher, 2023)
Learning style is one of the factors that influence student learning outcomes. Therefore the teacher must be able to know the student's learning style to make learning more optimal. This study aimed to identify the learning styles of students and non-student students in class X IPA SMA Plus Darul Hikmah Jember. This research uses a qualitative descriptive research type. The sample in this study was 23 class X IPA SMA Plus Darul Hikmah students, 16 of whom were Santri students and 7 of whom were non-santri students. Data were collected through observation, interviews, and distribution of learning style tests. The instrument used is a learning style test with a yes or no scale. This study identified three learning styles: visual, auditory, and kinesthetic. The data obtained were analyzed descriptively. The results of this study showed that of the 16 students, 43.75% had a visual learning style, 6.25% had an auditory style, and 50% had a kinesthetic learning style. At the same time, the data of non-santri students shows a visual learning style of 71.42%, an auditory learning style of 14.29%, and a kinesthetic learning style of 14.29%. From the results of this study, it is hoped that it can be used as evaluation material by teachers to improve learning methods so that differences in student learning styles can be overcome so that learning becomes more effective and optimal